أسس بناء المجتمع المتحضر: بحث في أساليب الشيخ محمد هاشم أشعري اللغوية في دعوته الكتابية - Moh. Ansori; Abd. Mujib Adnan (Proceedings of International Conference on Da'wa and Communication, 2019)
Since along time ago, Muslim scholars in Indonesia have made efforts to da’wa for building a civilized society for community of this part of the land, especially for their muslims. The greatest one of them was Sheikh Mohammed Hashim Ash'ari. He was the founder of Nahdlatul Ulama, one of the largest Islamic social organization in Indonesia. This research aimed to identify the beauty of language styles of his da’wa adopted from his writing Muqaddima al Qanun al Asasy. This research also analyze the principles of building a civilized society of Sheikh Mohammed Hashim Ash'ari’s thought. This research used the descriptive method and the techniques of reading and writing to collect and to classify data. Then to analyze those data used appropriate theories. The results of this research are that the language styles of da’wa of Sheikh Mohammed Hashim Ash'ari in his writing decorated with many types of magnificence, beauty and clear statement. These linguistic manifestations underlined his principles of building a civilized society and that are viewed from many terms used such as meeting, acquaintanceship, union, harmony, cooperation among all its members.